EFL practicum and classroom management among pre-service teachers at a public institution in Loja, 2023-2024 academic period - Arrobo García, Daniela Alejandra (2025)
Classroom management constitutes one of the fundamental pedagogical skills in the teaching practicum. The study aimed to explore the experiences of EFL pre-service teachers in classroom management during their practicum. Furthermore, this research sought to describe the challenges and identify the strategies implemented in classroom management in the teaching practice. The subjects under study included 25 EFL prospective teachers of a public institution in the city of Loja, Ecuador, throughout the 2023- 2024 academic period. Employing an exploratory design, the research used a mixed-method approach that comprised both quantitative and qualitative instruments. A questionnaire was applied to gather quantitative data about the challenges faced by student teachers. Contrastingly, qualitative information related to the strategies employed by the subjects to overcome classroom management issues was collected through a semi-structured interview. Subsequently, the data analysis was conducted as descriptive statistics for the quantitative questionnaire results, and content analysis for the interview responses. The findings indicated that most trainee teachers endure classroom management challenges predominantly associated with behavior and motivation. Moreover, the strategies were classified into four categories: instructional, behavioral, motivational, and reflective practice. Instructional strategies contemplated the effective use of time management, pre-service teachers’ voice, and student grouping in the delivery of instructions. Additionally, establishing clear classroom rules and consequences undisputedly helped to manage behavioural issues. Likewise, engagement activities and positive reinforcement were highly adopted as motivational strategies. Similarly, reflection processes alongside collaboration with peers and supervisors were reflective practices that guided improved classroom management in teaching performance. Overall, pre-service teachers’ experiences in classroom management were consolidated as challenging yet rewarding when successfully overcoming hurdles that led to fulfilment in seeing learners’ progress. Key Words: instructional strategies, behavioural challenges, motivational strategies, reflective practice